Bøger om jødisk historie i Danmark de sidste 15 år - Thing, Morten (Nordisk judaistik/Scandinavian Jewish Studies, 2016)
I Danmark er der de sidste femten år udkommet en hel del bøger om jødernes historie, ikke mindst om deres trængsler. Morten Thing gennemgår i denne oversigtsartikel de vigtigste indenfor forskning og formidling. * * *Books on Jewish history in Denmark the last 15 years • The most spectacular work about Jewish culture is without doubt Martin Schwarz Lausten’s six-volume work about the attitude of the Danish Lutheran church towards the Jews and Judaism. It is a work of great precision and with the use of many new sources. Although it is a work on church-history it has a lot to say on Jewish reactions to the church and the state. The volumes are: Kirke og synagoge,De fromme og jøderne, Oplysning i kirke og synagoge, Frie jøder?, Folkekirken og jøderne og Jødesympati og jødehad i folkekirken. Antisemitism has also been in focus and Sofie Lene Baks work on the history of antisemitism in Denmark is probably the most central: Dansk antisemitisme 1930–45. The rescue of the Danish Jews in WWII is without doubt the most researched topic in Danish Jewish history. Many new works have been published. Sofie Lene Baks book on what happened to the Jews when they came back from Sweden I 1945, Da krigen var forbi. It turned out that the municipality of Copenhagen had taken care of many flats and possessions. The history of the Jewish minority has been more in focus than ever. Many new books have been published. Arthur Arnheim’s Truet minoritet søger beskyttelse is the biggest book on the history from seventeenth century until today.